Effect of Aggressive Blood Pressure Control on the Recurrence of Atrial Fibrillation After Catheter Ablation: A Randomized, Open-Label Clinical Trial (SMAC-AF [Substrate Modification With Aggressive Blood Pressure Control]). Issue 19 (9th May 2017) - Parkash, Ratika; Wells, George A.; Sapp, John L.; Healey, Jeffrey S.; Tardif, Jean-Claude; Greiss, Isabelle; Rivard, Lena; Roux, Jean-Francois; Gula, Lorne; Nault, Isabelle; Novak, Paul; Birnie, David; et al.
Abstract : Background: Radiofrequency catheter ablation for atrial fibrillation has become an important therapy for AF; however, recurrence rates remain high. We proposed to determine whether aggressive blood pressure (BP) lowering prevents recurrent atrial fibrillation (AF) after catheter ablation in patients with AF and a high symptom burden. Methods: We randomly assigned 184 patients with AF and a BP >130/80 mm Hg to aggressive BP (target <120/80 mm Hg) or standard BP (target <140/90 mm Hg) treatment before their scheduled AF catheter ablation. The primary outcome was symptomatic recurrence of AF/atrial tachycardia/atrial flutter lasting >30 seconds, determined 3 months beyond catheter ablation by a blinded end-point evaluation. Results: The median follow-up was 14 months. At 6 months, the mean systolic BP was 123.2±13.2 mm Hg in the aggressive BP treatment group versus 135.4±15.7 mm Hg ( P <0.001) in the standard treatment group. The primary outcome occurred in 106 patients, 54 (61.4%) in the aggressive BP treatment group compared with 52 (61.2%) in the standard treatment group (hazard ratio=0.94; 95% confidence interval, 0.65–1.38; P =0.763). In the prespecified subgroup analysis of the influence of age, patients ≥61 years of age had a lower primary outcome event rate with aggressive BP (hazard ratio=0.58; 95% confidence interval, 0.34–0.97; P =0.013). There was a higher rate of hypotension requiring medication adjustment in the aggressive BP group (26% versus 0%). Conclusions: In this study, this duration of aggressive BP treatment did not reduce atrial arrhythmia recurrence after catheter ablation for AF but resulted in more hypotension. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00438113. Abstract : Supplemental Digital Content is available in the text.